The Influence of Fintech Adoption for Students Based on Theory of Planned Behavior (TPB) - Kamela, Hurian; Rasyiddin, Ahmad; Alam, Ryan Saputra; Sanusi, Abdullah (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2023)
The development of research in the world of technology, especially financial technology or fintech, provides novelty for this research. The limited research that discusses students' perceptions of fintech development is the main reason for this research. The objectives of this study are (1) to analyze the implementation of the influence of fintech adoption for students based on the Theory of Planned Behaviour (TPB) and (2) to quantitatively analyze the conditions regarding the influence of fintech adoption in the scope of students. This study aims to provide empirical evidence regarding the development of fintech in the scope of students in the Tangerang area. The research method uses primary data (questionnaires) from as many as 65 students. The results of the study prove that only Perceived Behavioural Control (PB) affects behaviour, that acceptance of technology is easier for students to understand, which is influenced by the scope of practice in the surrounding environment so that students commonly know the knowledge about fintech because of the wider development of technology. Students can make their own decisions about fintech adoption without being influenced by others.